African identity and Catholicism: two conflicting concepts in the intellectual journey of Alioune Diop (1956-1995) - (:unkn) unknown (My University, 2014)
The excitement which characterized Africa in the 1950s was largely due to the role of the West, for this was the work of African intellectuals trained in the Western intellectual tradition. Prominent among these intellectuals is Alioune Diop, who then became the leader of the cultural emancipation of Africa. By focusing on his figure, the thesis underlines the importance of intellectual biography as a working method in African history. It is presented there as an approach which makes it possible to grasp aspects which are often overlook in the study of events. Another characteristic of this work is the place given to unorganized archives and interviews. The dissertation presents a dimension of Alioune Diop's commitment that is less known, but which constitutes a key to understanding his life and work: Christian religion. Indeed, this African intellectual was particularly attentive to the dynamics of Christianity. He considered that religion as a reality which, in Africa, could help African peoples to overcome the challenges imposed by a context of decolonization, the Cold War, and multiple demands. Thus, in all the events he organized, the Christian religion and especially Catholicism, as the bearer of a particular cultural expression, had an important place. The dissertation stresses that the issues of the emancipation of African identity corresponded to the issues of an emancipation of Christianity in Africa from its determinants rooted exclusively in the cultural experience of the West. The thesis also demonstrates that Catholicism in its current dynamics in Africa inherited largely from the commitment of Alioune Diop and the intellectuals he managed to gather around him like Aimé Césaire, Léopold Sédar Senghor, Cheikh Anta Diop, Jacques Rabemananjara, and many others. This study is organized around the following questions, which are considered important: What is the exact contribution of Alioune Diop in reconciling the conflicting concepts of A
Keywords: African Research